Recurrent intestinal intussusception due to ileal angiolipoma: an uncommon, rare, and potentially life-threatening entity: a case report - Shu, Zheng; Li, Zhe; Lin, Shengnan; Yu, Haihua (Frontiers in Oncology, 2025)
Angiolipoma, a rare benign intestinal tumor, is primarily diagnosed through abdominal imaging and pathological examination. Intestinal angiolipomas frequently cause intussusception, necessitating prompt surgical resection. This paper reports a 62-year-old female patient admitted to the First Affiliated Hospital of Shandong First Medical University with “unprovoked paroxysmal abdominal pain for 3 months.” Preoperative diagnosis indicated ascending colonic intussusception secondary to ileal angiolipoma. Pathological examination following surgical bowel resection confirmed the lesion as an (ileal) angiolipoma. Given the rarity of this pathological entity in the intestinal tract, we present this case.